2008
DOI: 10.1161/circulationaha.107.752147
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy of Percutaneous Coronary Intervention With Stenting and Coronary Artery Bypass Surgery for Multivessel Coronary Artery Disease

Abstract: Background-Randomized trials that studied clinical outcomes after percutaneous coronary intervention (PCI) with bare metal stenting versus coronary artery bypass grafting (CABG) are underpowered to properly assess safety end points like death, stroke, and myocardial infarction. Pooling data from randomized controlled trials increases the statistical power and allows better assessment of the treatment effect in high-risk subgroups. Methods and Results-We performed a pooled analysis of 3051 patients in 4 randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
157
0
16

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(180 citation statements)
references
References 45 publications
5
157
0
16
Order By: Relevance
“…After 5 years of follow-up, the meta-analysis did not show any significant differences in rates of survival between the CABG and PCI groups, 34 although other studies have shown differences in mortality. [10][11][12] Second, the use of medication differed between the groups in our study, reflecting variations in standard care of patients between the two treatment groups. Third, more patients withdrew, after randomization, from the CABG group than from the PCI group.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…After 5 years of follow-up, the meta-analysis did not show any significant differences in rates of survival between the CABG and PCI groups, 34 although other studies have shown differences in mortality. [10][11][12] Second, the use of medication differed between the groups in our study, reflecting variations in standard care of patients between the two treatment groups. Third, more patients withdrew, after randomization, from the CABG group than from the PCI group.…”
mentioning
confidence: 83%
“…Others have shown a significant long-term survival advantage with surgery (e.g., the Stent or Surgery [SOS] study). [10][11][12] Studies comparing PCI involving drugeluting stents with CABG have generally been smaller and nonrandomized. [13][14][15][16][17][18][19][20][21][22][23][24] Data from randomized, controlled trials of drug-eluting stents as compared with bare-metal stents have shown significant reductions in the rate of repeat intervention, with similar rates of death and myocardial infarction.…”
mentioning
confidence: 99%
“…3) In such situation, the most critical form is called ischemic cardiomyopathy (ICM), which is characterized by poor prognosis despite various treatments. 4,5) Additionally, it was demonstrated that concomitant functional MR is one of the risk factors for long-term survival in ischemic heart disease. 6,7) Thus, ICM with functional MR is the most critical combination and the definitive treatment is heart transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Recent randomized controlled trials have shown that overall major adverse cardiac and cerebrovascular events (MACCE) are lower with CABG than PCI in patients revascularized for unprotected LM-3VD. [13][14][15][16][17][18] However, the outcomes of CABG and PCI were similar in patients who have focal disease with SYNTAX score ≤ 22. 18,19 Due to the more invasive nature and higher shortterm morbidity of CABG, PCI has been empirically considered a good alternative to CABG in patients who are deemed a high surgical risk.…”
mentioning
confidence: 98%